Cancer organoid co-culture model system: Novel approach to guide precision medicine - Yuan, Jin; Li, Xiaoyang; Yu, Shengji (Frontiers in Immunology, 2023)
Three-dimensional cancer organoids derived from self-organizing cancer stems are ex vivo miniatures of tumors that faithfully recapitulate their structure, distinctive cancer features, and genetic signatures. As novel tools, current cancer organoids have been well established and rapidly applied in drug testing, genome editing, and transplantation, with the ultimate aim of entering clinical practice for guiding personalized therapy. However, given that the lack of a tumor microenvironment, including immune cells and fibrous cells, is a major limitation of this emerging methodology, co-culture models inspire high hope for further application of this technology in cancer research. Co-culture of cancer organoids and immune cells or fibroblasts is available to investigate the tumor microenvironment, molecular interactions, and chimeric antigen receptor-engineered lymphocytes in cancer treatment. In light of the recent progress in cancer organoid co-culture models, it is only possible to recognize the advantages and drawbacks of this novel model to exploit its full potential. In this review, we summarize the recent advances in the application of cancer organoids and co-culture models and how they could be improved in the future to benefit cancer research, especially precision medicine.